LIABILITY OF CRIMES AGAINST JUSTICE: CONDITIONS AND CAUSES OF FINDINGS, METHODS OF DETERMINATION - Ахмедов, Вусал Алігісмат огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: to reveal the concept and characteristics of the latency of crimes against justice as one of the elements of assessing the real level of crime in this area. Methods of research: the methodological basis of the study were general scientific methods of cognition, which helped to find out the objective patterns of occurrence and mechanisms for detecting latent crimes against justice. Results: the author identifies a set of prerequisites for a high level of latency of crimes against justice and formulates a system of mechanisms for detecting such crimes. Discussion: the author proposes to distinguish unknowing latent crime from the recognizable. Discusses the thesis on the prevailing knowledge of latent crimes against justice, which is of practical importance for developing a system of crime prevention measures in this area. Summing up, we note that the causes of latency in crimes against justice differ significantly from other types of crimes. First of all, there is a shameful principle of corporate solidarity of lawyers, because the overwhelming majority of complaints of victims of unlawful detention, forcing to testify, remain without consideration, or result in only disciplinary action, without opening a criminal proceeding and transferring a case to court. Also, the reasons for the latency of crimes in the field of justice can be attributed to the general low degree of evidence of committed acts; professional competence of the subject of a crime, allowing him to effectively hide a criminal offense; on the activity of the guilty regarding the concealment of a criminal offense, etc.); the lack of proper response from law enforcement agencies to the information disclosed about violence, cases of concealment of criminal offenses committed, etc. Detection of latent crime against justice is important for developing an effective system of crime prevention measures and possible through statistical, sociological, logical-mathematical, economic and political methods.